Bennington and the Green Mountain Boys The Emergence of Liberal Democracy in Vermont, 1760-1850 - Shalhope, Robert E. (Johns Hopkins University Press, 2020)
In this lively study, Robert E. Shalhope supplies a fascinating microcosmic view of the rise and triumph of liberal individualism in America and explores its impact on political culture.Selected by Choice Magazine as an Outstanding Academic TitleOriginally published in 1996. Americans who lived between the Revolution and Civil War felt the brunt of resounding and sometimes frightening changes, which together eventually influenced the political culture of early America. In this lively study, Robert E. Shalhope examines one of the changes most difficult to gauge and most controversial among students of the period-the rise and triumph of liberal individualism in America-and explores its impact on political culture.Taking Bennington, Vermont, and its environs as a case study, Shalhope untangles the clash among three competing elements in the community-the egalitarian communalism of the Strict Congregationalists; the democratic individualism of the revolutionary Green Mountain Boys; and the hierarchical authority of the community's Federalist gentlemen of property and standing. None of these players anticipated (and indeed did not wish for) the result-the emergence of democratic liberalism. Shalhope writes of class tension, economic competition, and religious differences-and ultimately of cultural conflict and political partisanship-and yet throughout uses individual life experiences to give the narrative piquancy and to emphasize the significance of seemingly small, personal decisions. Shalhope thus demonstrates how the private lives of ordinary people played a role in the settlement of public issues.As an account of a single town and how its residents responded to change, Bennington and the Green Mountain Boys supplies a fascinating microcosmic view of the larger story of how liberal America came to be.